2020
DOI: 10.1101/2020.09.29.319293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A preferential role for ventromedial prefrontal cortex in assessing “the value of the whole” in multi-attribute object evaluation

Abstract: Everyday decision-making commonly involves assigning values to complex objects with multiple value-relevant attributes. Drawing on what is known about complex object recognition, we hypothesized two routes to multi-attribute evaluation: assessing the value of the whole object based on attribute configuration, or summing individual attribute-values. In two samples of healthy human participants undergoing eye-tracking and fMRI while evaluating novel pseudo-objects, we found evidence for distinct forms of multi-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…If value is reflected in signals carried at different stages of the VVS, could it be that value construction for multi-attribute options is at least partially occurring within the VVS? We provided some evidence that this might be the case; in the PRC, the region within the VVS with the most complex configural representations, fMRI activation tracked the value of objects more in a configural compared to an elemental value construction condition (Pelletier et al, 2020). This modulatory effect of value construction condition on value representations in the PRC suggests an involvement of the VVS in value construction, which requires interactions with the OFC/vmPFC when value is inferred from the configural association between attributes.…”
Section: The Contribution Of Ofc/vmpfc To Multi-attribute Value Const...mentioning
confidence: 90%
See 1 more Smart Citation
“…If value is reflected in signals carried at different stages of the VVS, could it be that value construction for multi-attribute options is at least partially occurring within the VVS? We provided some evidence that this might be the case; in the PRC, the region within the VVS with the most complex configural representations, fMRI activation tracked the value of objects more in a configural compared to an elemental value construction condition (Pelletier et al, 2020). This modulatory effect of value construction condition on value representations in the PRC suggests an involvement of the VVS in value construction, which requires interactions with the OFC/vmPFC when value is inferred from the configural association between attributes.…”
Section: The Contribution Of Ofc/vmpfc To Multi-attribute Value Const...mentioning
confidence: 90%
“…A follow-up fMRI investigation using the same stimuli and conditions in healthy participants found that hemodynamic signal in medial OFC tracked the value of whole objects in the configural condition but was not consistent with a role for this region in elemental value integration (Pelletier et al, 2020). These complementary studies converge to support the claim that the neural substrates of multi-attribute object evaluation are at least partially distinct under these two conditions, with OFC/vmPFC specifically engaged in the configural condition.…”
Section: The Contribution Of Ofc/vmpfc To Multi-attribute Value Const...mentioning
confidence: 99%
“…, 2017 ; de Berker et al. , 2019 ; Pelletier et al. , 2021 ), this approach combines two methodological advantages:…”
Section: Introductionmentioning
confidence: 99%